2009
DOI: 10.1007/s00204-009-0416-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian epoxide hydrolases in xenobiotic metabolism and signalling

Abstract: Epoxide hydrolases catalyse the hydrolysis of electrophilic-and therefore potentially genotoxic-epoxides to the corresponding less reactive vicinal diols, which explains the classiWcation of epoxide hydrolases as typical detoxifying enzymes. The best example is mammalian microsomal epoxide hydrolase (mEH)-an enzyme prone to detoxiWcation-due to a high expression level in the liver, a broad substrate selectivity, as well as inducibility by foreign compounds. The mEH is capable of inactivating a large number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 226 publications
(219 reference statements)
3
143
0
Order By: Relevance
“…In recent years, sEH has attracted attention due to its role in the turnover of lipid derived epoxides, which are signaling lipids with functions in regulatory processes such as the control of blood pressure, inflammatory processes and cell proliferation. Furthermore, sEH is thought to be a promising target for pharmacological inhibition to treat hypertension and possibly other diseases (3). mEH classically plays a major role in xenobiotic metabolism and has been described as a biotransformation enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, sEH has attracted attention due to its role in the turnover of lipid derived epoxides, which are signaling lipids with functions in regulatory processes such as the control of blood pressure, inflammatory processes and cell proliferation. Furthermore, sEH is thought to be a promising target for pharmacological inhibition to treat hypertension and possibly other diseases (3). mEH classically plays a major role in xenobiotic metabolism and has been described as a biotransformation enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the mammalian microsomal epoxide hydrolase (meH) plays a key role in xenobiotic metabolism. The main function of mEH is the breakdown of genotoxic and carcinogenic epoxides to less harmful metabolites and the protection of macromolecules from the electrophilic attack of reactive intermediates (3). However, in the case of some polycyclic aromatic hydrocarbons, such as benzo(a)pyrene, present in tobacco smoke, dihydrodiol formation stabilizes bay-region epoxides, increasing the mutagenic and carcinogenic potential of the product (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…101 One xenobiotic metabolizing enzymes identified with a variant allele linked to petroleum oil herbicide exposure and a higher prostate cancer risk was found in the gene that encodes microsomal epoxide hydrolase, which is an important detoxication enzyme of reactive epoxides. 27 Epoxides are chemicals that are formed via cytochrome P450-mediated monooxygenation of carcinogens, such as benzo(a)pyrene found in cigarette smoke and aflatoxin B1, which is produced by the mold Aspergillus flavus. Epoxides produced in vivo are often chemically unstable and can covalently modify DNA, thus forming DNA adducts with a propensity to cause mutation.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Nonetheless, in biological systems opening of the epoxide ring is likely to occur on exposure to peroxidases, in which case the products will be fatty acid triols. The same triols could arise also from hydrolysis of the precursor hydroperoxy-epoxides, which are likely substrates for epoxide hydrolase ( 35 ).…”
Section: Comparison and Contrast With Autoxidative Formation Of Endopmentioning
confidence: 99%